INTEREST RATE SPREAD IN KENYA: RESULTS OF A SURVEY OF COMMERCIAL BANKS - Barako, Dulacha; Ali, Abdinasir (The journal of contemporary issues in business and government, 2009)
This paper examines interest rate spread in Kenya and seeks to address Eastern African region concerns on this subject by drawing on one country’s experience. This is a qualitative study that examines determinants of interest rate spread based on opinion surveys of staff from commercial banks in Kenya. Results of the data analysis indicate that the two most significant predictors of interest rate spread are provision for bad debts and administrative costs. Banks suggest various remedies for reducing interest rate spread, particularly an overhaul of the judicial review process to address cases relating to bad debts and the establishment of Credit Reference Bureaus. A number of policy recommendations are discussed.